U.S. REIT industry profitability: a Bennet decomposition of industry dynamics - Feng, Zhilan; Miller, Stephen M.; Tirtiroglu, Dogan (International Journal of Strategic Property Management, 2021)
This paper considers the aggregate profitability performance of the REIT industry. The aggregate performance depends on the underlying microeconomic dynamics within an industry – the growth of individual REITs (the within effect), the reallocation between existing REITs (the between effect), the entry of new REITs (the entry effect), and the exit of the existing REITs (the exit effect). We apply an extended Bennet (1920) dynamic decomposition on the REIT industry’s return on equity (ROE) and study the annual data on U.S. Equity REITs for the 1989 to 2015 period and various REIT industry specific sub-sample periods. Bailey et al.’s (1992) and Haltiwanger’s (1997) dynamic industry performance decompositions are special cases of the Bennet decomposition. The “within” and “between” effects dominate the annual changes in this industry’s ROE. To the extent that our Equity REIT sample proxies for the FTSE NAREIT All Equity Index, our conclusions also relate to this index’s profitability performance between 1989 and 2015.